Screening Endoscopy Contributes to Relevant Modifications of Therapeutic Regimen in Children With Intestinal Failure. Issue 4 (October 2018) - Busch, Andreas; Sturm, Ekkehard
ABSTRACT: Objective: The role of endoscopy in the diagnostic workup of children with intestinal failure (IF) is not well defined. It is unclear whether endoscopies should be performed as a screening procedure or only upon manifestation of symptoms. The aim of this study is to evaluate, whether performing screening endoscopy contributes to clinical management in children with IF. Methods: Comparative retrospective case series study in children with IF (mean age 70.4 months ± 58.4 months) presenting for diagnostic workup in a single intestinal rehabilitation center. Endoscopies were performed either as a screening procedure (Group 1, n = 45) or as indicated by symptoms of gastrointestinal dysfunction (Group 2, n = 11). Results: A total of 92 endoscopies (56 esophagogastroduodenoscopies; 12 enteroscopies; 24 colonoscopies) were performed in 56 children. IF etiology included short bowel syndrome (n = 37), motility disorder (n = 16), and mucosal enteropathy (n = 3). Comparing Group 1 with Group 2 abnormal endoscopic findings were detected in 66.7% versus 81.8%. Findings led to adaptation of therapeutic regimes in 64.7% versus 85.7%. We detected a higher rate of erosive and ulcerative gastritis and duodenitis, enteritis, and colitis in Group 1 compared to Group 2. Conclusions: Endoscopy in children with IF frequently reveals abnormal findings, leading to recommendations for treatment adaptation in the majority of cases, irrespective of whether endoscopy has been performed as a screening procedure or as indicated by symptoms. Using endoscopy as a screening tool may improve both, the detection of gastrointestinal pathology and the clinical management of children with IF.